Preparation, Ignition, and Combustion of Mg·S Reactive Nanocomposites. Issue 8 (2nd August 2016) - Abraham, Ani; Zhong, Ziyue; Liu, Ruodong; Grinshpun, Sergey A.; Yermakov, Michael; Indugula, Reshmi; Schoenitz, Mirko; Dreizin, Edward L.
ABSTRACT: Elemental magnesium and sulfur powders were ball milled to prepare a nanocomposite material, Mg·S. Ignition of the prepared powder was characterized using both a heated filament experiment and electric spark. Combustion of individual particles was studied by injecting the powder into a premixed hydrocarbon-air flame. Combustion of powder clouds was examined using a constant volume explosion chamber. Biocidal effect of the produced combustion products against aerosolized endospores of Bacillus thuringiensis (simulant of Bacillus anthracis ) was quantified. The powders ignited at lower temperatures, compared to pure magnesium. Delayed ignition was observed for powders initiated by spark and for powder clouds ignited in a constant volume chamber by a heated wire. The delay is likely due to the formation of an evaporated sulfur cloud preceding ignition. The composite material burned faster than pure magnesium, which was shown by shorter measured burn times for individual particles, and by higher rates of pressure rise in the constant volume explosion experiments. The optical emission spectra produced by burning Mg·S nanocomposite powders exhibited an unusually strong emission at short wavelengths; additional spectroscopic studies of such flames are of interest. Combustion products generated by Mg·S composite powders effectively inactivated aerosolized spores; the effectiveness of inactivation was comparable to some previously examined formulations, including aluminum-based composite powders containing iodine.